Revisiting lymph node staging in the 9th TNM Classification for lung cancer: a bronchoscopic perspective - Brock, Judith; Herth, Felix (Respiration, 2025)
Background: The TNM staging system is the cornerstone of lung cancer classification, providing a framework for prognosis and treatment planning in a universal nomenclature. The 9th edition of the TNM classification, released by the International Association for the Study of Lung Cancer (IASLC) and went into effect in January 2025, introduces refinements to lymph node (N) staging. Lymph node staging is performed minimally invasively using bronchoscopy with endobronchial ultrasound (EBUS). This article explores the latest updates on lymph node staging by EBUS and their implications for lung cancer management from the perspective of bronchoscopy. Summary: The 9th edition of the TNM classification includes the subdivision of N2 lymph nodes into N2a single-station and N2b multiple-station involvement, but not the subdivision of N1 lymph nodes. This has implications not only for treatment but also for the number of lymph nodes sampled by EBUS. As there is no strict hierarchy of N2 lymph nodes, this poses challenges to the order in which N2 lymph nodes should be sampled. The development of a new thin EBUS device will enable sampling of peripheral N1 lymph nodes. This could influence future TNM classifications, given that there are pathological but not clinical differences in survival between purely peripheral and hilar N1 involvement. Key Messages: With respect to occult lymph node disease, EBUS remains fundamental in staging lung cancer. New technical developments will also enable sampling of peripheral N1 lymph nodes.